Normalized Difference Vegetation Index (NDVI) for soybean biomass and nutrient uptake estimation in response to production systems and fertilization strategies - Farias, Gustavo Duarte; Bremm, Carolina; Bredemeier, Christian; de Lima Menezes, Jeferson; Alves, Lucas Aquino; Tiecher, Tales; Martins, Amanda Posselt; Fioravanço, Gabriela Paiva; da Silva, Gabriela Petry; de Faccio Carvalho, Paulo César (Frontiers in Sustainable Food Systems, 2023)
The system fertilization approach emerged to improve nutrient use efficiency in croplands. This new fertilization concept aims at taking advantage of nutrient cycling within an agroecosystem to obtain maximum production from each nutrient unit. To monitor this effect, methodologies such as the Normalized Difference Vegetation Index (NDVI) are promising to evaluate plant biomass and nutrient content. We evaluated the use of NDVI as a predictor of shoot biomass, P and K uptake, and yield in soybean. Treatments consisted of two production systems (Integrated crop-livestock system - ICLS and Cropping system - CS), and two periods of phosphorus and potassium fertilization (Crop fertilization - P and K applied at soybean sowing - and System fertilization - P and K applied in the pasture establishment). NDVI was evaluated weekly from the growth stage V2 up to growth stage R8, using the Greenseeker canopy sensor. At the growth stages V4, V6, R2 and R4, plants were sampled after NDVI evaluation for chemical analysis. Soybean yield and K uptake were similar between production systems and fertilization strategies (P > 0.05). Soybean shoot biomass and P uptake were, respectively, 25.3% and 29.7% higher in ICLS compared to cropping system (P < 0.05). For NDVI, an interaction between production system and days after sowing (P < 0.05) was observed. NDVI increased until 0.95 at 96 days after sowing in CS and until 0.92 at 92 days after sowing in ICLS. A significant relationship between NDVI and shoot biomass, P and K uptake was observed (P<0.05). Our results show that the vegetation index NDVI can be used for estimating shoot biomass, P and K uptake in early growth stages of soybean crops, providing farmers with a new tool for evaluating the spatial variability of soybean growth and nutrition.